Rare Genetic Syndromes and Oral Anomalies: A Review of the Literature and Case Series with a New Classification Proposal - Claudia Salerno; Valeria D'Avola; Luca Oberti; Elena Almonte; Elena Maria Bazzini; Gianluca Martino Tartaglia; Maria Grazia Cagetti (MDPI AG, 2021)
Rare genetic syndromes, conditions with a global average prevalence of 40 cases/100,000 people, are associated with anatomical, physiological, and neurological anomalies that may affect different body districts, including the oral district. So far, no classification of oral abnormalities in rare genetic syndromes is present in the literature. The aim of this narrative review is to analyze literature on rare genetic syndromes affecting dento-oro-maxillofacial structures (teeth, maxillary bones, oral soft tissues, or mixed) and to propose a classification according to the detected oral abnormalities. In addition, five significant cases of rare genetic syndromes are presented. The Scale for the Assessment of Narrative Review Articles (SANRA) was followed for this review. From 674 papers obtained through PubMed search, 351 were selected. Sixty-two rare genetic syndromes involving oral manifestations were found and classified. The proposed classification aims to help the clinician to easily understand which dento-oro-maxillofacial findings might be expected in the presence of each rare genetic syndrome. This immediate framework may both help in the diagnosis of dento-oro-maxillofacial anomalies related to the underlying pathology as well as facilitate the drafting of treatment plans with the involvement of a multidisciplinary team.